Business acumen for strategic communicators : the workbook - Ragas, Matthew; Culp, Ron (Emerald Publishing Limited, 2024)
Business fluency is essential today for effective strategic communication. To fulfill the mandate of trusted counselors and advisors to executives and the C-suite, communication professionals must no longer just have excellent communication skills, but they must understand and speak the language of the business world. The challenge is that many communication graduates and professionals did not go to business school and do not hold an MBA. Business Acumen for Strategic Communicators: The Workbook provides the essential practical learning needed to help upskill communication professionals into bona fide business leaders and advisors. Through briefs, exercises and discussion activities, readers will learn to analyze and interpret key business materials produced by companies and nonprofit organizations, including CEO letters, annual reports, financial statements, earnings releases, CSR, DEI and ESG reports, and more. A revised and expanded glossary is provided, as are answer keys for the exercises. Drawing on the success of Ragas and Culp's prior books, this innovative workbook offers hands-on learning opportunities to help put newly acquired business acumen knowledge into practice.